Frequency of Celiac Disease in Microcytic Anemia Patients of Nowshera - Hamid Ullah, Liaqat Ali, Mujahid Aslam, Muhammad Naeem, Muhammad Imran Ullah, Abbas Masood, Assad Ullah, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Celiac disease a chronic gastrointestinal disorder is caused by an immune response to the gluten. Numerous studies have been conducted worldwide on the relationship between anemia and celiac disease. Objective: To find out the frequency of celiac disease in microcytic anemia patients of Nowshera Methodology: The current study was cross sectional carried out at the Gastroenterology department, Qazi Hussain Ahmad Medical Complex, Nowshera from October 2021 to October 2022. For serological diagnosis of the celiac disease, all the patients were tested for IgA and IgG tTG (anti-tissue transglutaminase). OesophagoGastroDuodenoscopy (OGD) was done for all the patients with raised level of IgA and IgG tTG (anti-tissue transglutaminase). All the analysis of collected data was done by employing IBM SPSS version 24. Results: In this study a total of 300 patients with microcytic anemia were enrolled. There were 165 (55%) female participants while 135 (45%) patients were male. IgA and IgG tTG (anti-tissue transglutaminase) levels were raised in 15 (5%) patients amongst 300 patients with microcytic anemia. In duodenal biopsy of 15 patients with celiac disease, Marsh I was observed in 4 (33.33%) patients, Marsh II in 5 (41.67%) patients, Marsh III in 3 (25%) patients, while 3 (20%) cases showed normal histo-pathological findings. Thus the overall frequency of celiac disease amongst microcytic anemia patients was 15 (5%). Conclusion: Our study concludes that celiac disease is more prevalent amongst the patients with microcytic anemia. The microcytic anemia can be considered as additional gastrointestinal manifestation of the celiac disease. Keywords: Frequency; Celiac disease; Microcytic anemia